1991
DOI: 10.1111/j.1476-5381.1991.tb12169.x
|View full text |Cite
|
Sign up to set email alerts
|

New, long‐acting, potent bradykinin antagonists

Abstract: Hyp3-D-Tic7-Oic8-BK (compound II), and Arg(Tos)'-Hyp3-Thi5-D-Tic7-Oic8-BK (compound III), were tested against the effects of BK in 9 bioassay preparations including visceral smooth muscles, vasoconstriction, plasma protein extravasation, release of prostaglandin E2, bronchoconstriction, and stimulation of afferent C-fibre nociceptors. In some of these tests the effects of the new compounds were compared with those of the antagonist D-Arg0-Hyp2-Thi5'8-D-Phe7-BK (compound IV), described by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
96
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(106 citation statements)
references
References 18 publications
8
96
0
Order By: Relevance
“…Similarly, no tachyphylaxis occurred with BK while Hoe 140 produced a small vasodepressor response which could not be reproduced at the second and third injection. Since the direct effect of Hoe 140 on blood pressure is much smaller than that evoked by BK, the blockade of the BK response by Hoe 140 is probably related to a pharmacological antagonism as reported earlier Hock et al, 1991;Lembeck et al, 1991).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, no tachyphylaxis occurred with BK while Hoe 140 produced a small vasodepressor response which could not be reproduced at the second and third injection. Since the direct effect of Hoe 140 on blood pressure is much smaller than that evoked by BK, the blockade of the BK response by Hoe 140 is probably related to a pharmacological antagonism as reported earlier Hock et al, 1991;Lembeck et al, 1991).…”
Section: Discussionsupporting
confidence: 56%
“…Selective (Regoli & Barabe, 1980) Hock et al, 1991;Bao et al, 1991;Lembeck et al, 1991;Rhaleb et al, 1992 (Barabe et al, 1979;Taylor et al, 1989). Moreover, unlike the endothelial B2 receptor, canine muscular B, and B2 receptors mediate relaxation of the arterial smooth muscle by promoting the release of prostaglandins (Rhaleb et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In radiogland binding studies D-Arg-[Hyp3,Thi5,D-Tic7,0ic8]BK (Hoe 140) was reported to displace BK with a K, value of 8 x 101°M . In isolated tissue assays, Hoe 140 antagonized the action of BK at the BK2-receptor with pA2 values ranging from 9.3 in the rat uterus to 8.1 in the guinea-pig ileum (Lembeck et al, 1991;Hock et al, 1991). The compound was reported to be devoid of activity at the BK1 receptor .…”
Section: Introductdonmentioning
confidence: 99%
“…Icatibant has been shown to be inactive against a great variety of mediators including angiotensin II, noradrenaline, histamine, acetylcholine, 5-hydroxytryptamine, substance P and neurokinin A (Lembeck et al, 1991;Wirth et al, 1991;Damas & Remacle-Volon, 1992;Rhaleb et al, 1992). Since icatibant does not inhibit the action of des-Arg9-BK at the B1 receptor Rhaleb et al, 1992), the present results point towards an involvement of B2, but not B. receptors in collagenase-induced paw oedema.…”
Section: Discussionmentioning
confidence: 52%
“…For reasons of clarity only the first 30 min after the collagenase injection are given in the graph; thereafter, until the end of the observation period, the difference in the sensitivity scores for rats pretreated with icatibant and for control rats remained unchanged (*P <0.02 mammalian collagenases in their mode of action (Hatheway, 1990). Clostridial collagenases act on all known types of collagen and can cleave native triple helical collagen into small fragments, mostly tripeptides, whereas mammalian collagenases are specific for certain types of collagen and often cleave only one protein bond in a polypeptide chain of triple helical collagen, resulting in two polypeptide fragments (Han et al, 1992 (Lembeck et al, 1991) or Hoe-140 Wirth et al, 1991)], caused a pronounced reduction of the collagenaseinduced paw oedema and of plasma protein extravasation. In addition, icatibant abolished the increase in sensitivity scores in a behaviour test after subplantar injection of collagenase in unanaesthetized rats.…”
Section: Discussionmentioning
confidence: 99%